2003
DOI: 10.1046/j.1365-294x.2003.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating population sizes for elusive animals: the forest elephants of Kakum National Park, Ghana

L. S. Eggert,
J. A. Eggert,
D. S. Woodruff

Abstract: African forest elephants are difficult to observe in the dense vegetation, and previous studies have relied upon indirect methods to estimate population sizes. Using multilocus genotyping of noninvasively collected samples, we performed a genetic survey of the forest elephant population at Kakum National Park, Ghana. We estimated population size, sex ratio and genetic variability from our data, then combined this information with field observations to divide the population into age groups. Our population size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
221
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(234 citation statements)
references
References 58 publications
(72 reference statements)
7
221
3
1
Order By: Relevance
“…The advent of permanent marking techniques such as genetic 'tagging' (e.g. Feldheim et al 2002, Mowat & Paetkau 2002, Eggert et al 2003 for whale sharks will permit validation of our model predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of permanent marking techniques such as genetic 'tagging' (e.g. Feldheim et al 2002, Mowat & Paetkau 2002, Eggert et al 2003 for whale sharks will permit validation of our model predictions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, traditional CMR methods that require trapping or handling of individuals may harm the animals. For difficult-to-observe species, noninvasive genetic surveys have in recent years provided valuable information for the management and monitoring of populations [7][8][9][10][11][12][13]. These studies showed that use of molecular census techniques may reduce time and effort and provide more detailed information about elusive species [14].…”
mentioning
confidence: 99%
“…The method can easily be up-scaled to larger mammals like elephants, 27 tigers and hornbills 28 of conventional concern to Thai conservationists. This would provide wildlife managers with a new tool to assess a population' s viability and opens up numerous research opportunities, as habitat fragmentation is such a ubiquitous phenomenon.…”
Section: Discussionmentioning
confidence: 99%